Legal Regulation of Upgrade Qualification of Pedagogical Workers of Secondary Schools of Ukraine (1990-s – beginning of the XXI century) - Solovei, Mykola (Pedagogical Discourse, 2016)
The article analyzes the legislation of Ukraine on the regulation of training of secondary school teachers. In the early 1990s Ukraine adopted the Laws «On Education» and «On General Secondary Education». These laws have defined the development of education in Ukraine after the collapse of the Soviet Union. The Article 47, paragraph 2 of the Law «On Education» examines teacher training as the expansion and updating of professional knowledge and skills. This is reflected in other laws of Ukraine. In particular: «On Pre-School Education» (article 25) «On the Non-Formal Education» (Article 24), «On Education» (Article 29). According to Article 56 of the Law «On Education» the State creates the appropriate conditions for training. High school teachers improve knowledge and skills once in five years prior to certification. Orders are formed by district departments of education (Law «On Education» (Article 47 § 3). The form and content of the training programs are defined by In- Service Teacher Training Institutes. In Ukraine, several groups of sub-standard documents are created: A) strategies and regulatory documents; B) affecting the organization, management and licensing of educational programs; C) documents on methodology and standardization of educational content. In particular: the National Programme « Education of the 21st Century», the National Doctrine of the Development of Education of the 21st Century, Regulations on the In-Service Training Institutes (2000); the Concept of Teacher Education Development in Ukraine (2004), the State Programme «Teacher» (2002); Programmes of Improving the Quality of Science and Math Education (2009), the Development of Pre-school Education (2011); Standards of Primary School, Basic and Upper Secondary Education (2012). Draft Law of Ukraine «On Education» (2015) considers the professional development of teachers in terms of formal, informal and unformal adult education. The law specifies that the training is the right (Article 45 to claim 15), and the duty of teachers (Article 45 section 2.1.). The law provides freedom of choice of educational programs, forms of training, education. In general, improvement of qualification of teachers is sufficiently reflected in the legislation of Ukraine. At the same time in the process of updating the legislation of Ukraine it is advisable further studies of institutional development training in the context of European legislation, the study of training in the context of the certification of teachers, modeling professional development of specialists in the modern educational process. Key words: constitution, law, training, attestation, certification, methodological work, continuing education.